(untitled) (Journal of the College of Basic Education, 2022)
This study was designed to isolate the most important bioactive compounds from the Iraqi plant Teucrium polium using a liquid-liquid extraction method, detected on thin layer chromatography (TLC) plates, and examine the antimicrobial activities Teucrium polium extracts against five bacterial species by using disc-diffusion method. The extracts were identified via Thin Layer Chromatography (TLC) using a mixture of ethyl acetate : methanol : water (100 : 15 : 10). as chromatographic eluent .